Analysis of the Effect of Adding PNP Phototransistors on Fiber Optic Systems - Faisal Arrasyid (Brilliance: Research of Artificial Intelligence, 2022)
This study analyzes the performance of PNP phototransistors made of Gallium Arsenide (GaAs) and Silicon (Si). Based on the analysis for gallium arsenide and silicon PNP phototransistors, the emitter current at the output is greater than the photon current at the incident. With?= 1017?3;?= 1016?3and?= 1019?3;?= 1016?3The input current for GaAs material is 1.6865×10?7 ., respectively?and 8.0331×10?6A. With the addition of internal gain on the GaAs material, namely; common-base internal gain (?)= 0.9991; 0.8974 and the common-emitter internal gain(?)=1125; 8.7488, then each output current is 1.8973×10?4?and 7.028×10?5?. With the addition of the internal gain on the phototransistor, we get SNR = 26256 and 8022.As for the silicone material with?= 1017m3;?= 1016?3and?= 1019?3;?= 1016?3the input current and output current are respectively 1.0766×10?7?and 1,266×10?6?. With the internal gain on the silicon material, namely; for common-base internal gain(?)=0.9994; 0.9220 and the common-emitter internal gain(?)= 1563; 11,818, then the output currents are 1.6831×10?4A and 1.4827×10?5A, respectively. With the addition of the internal gain, the SNR for silicon is 8.3766×10?5 and 3.3609×10?6, respectively.